Pedagogia Histórico-Crítica: uma teoria pedagógica desideologizante - Silva, Maycon Henrique da (2025)
This dissertation aims to analyze the relationships between the Marxist concept of ideology and Historical-Critical Pedagogy. We seek to answer the following question: Is it possible to state that Historical-Critical Pedagogy constitutes a de- ideologizing pedagogical theory? In order to answer this question, based on a bibliographical research in classic and contemporary references of Marxism, this dissertation was organized into three sections: The first is composed of a historical analysis of the concept of ideology from its earliest use to the way it is understood today, focusing especially on the Marxist conception of the term. We analyze the conception of ideology present in the works of five classic authors of Marxism: Marx, Engels, Lenin, Gramsci and Althusser and point out the changes and continuities that exist in relation to the Marxist conception of ideology. In the second, taking as a premise the concept of ideology developed by Marx and Engels, we seek to point out the relationship between ideology and education and the way in which ideological thought uses education as an instrument for its dissemination and perpetuation in society. To this end, we problematize two major strands of ideology present in Brazilian education today: the ideology of competence that materializes in the production of the National Common Curricular Base and the ideology of “neutral” knowledge that materializes in the proposal of the Escola Sem Partido project. In the third section, we present Historical-Critical Pedagogy as a Marxist-based pedagogical theory that aims to produce a new consciousness for a new society. In other words, its proposal is based on the clarity that, through the act of education and despite hegemonic (ideological) conceptions of education, it is possible to work inside and outside the school towards the undoing of ideological thinking towards the production of a philosophical consciousness, critical thinking and a worldview that faithfully understands objective reality and its contradictions. Therefore, in agreement with Marx and Engels, Historical-Critical Pedagogy is engaged in the struggle to overcome the capitalist mode of production as much as to destroy ideology, since it is clear that revolutionary practice requires a revolutionary theory. We conclude, therefore, that, with regard to education, Historical-Critical Pedagogy, up to the present moment, fulfills the role of revolutionary pedagogical theory and, consequently, is characterized as a de-ideologizing pedagogical theory.